THE PROGNOSTIC VALUE OF THE GASTROINTESTINAL FAILURE SCORE IN PATIENTS WITH ACUTE PANCREATITIS TREATED AT THE CENTER FOR CRITICAL CARE MEDICINE, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the prognostic value of gastrointestinal failure, assessed by the gastrointestinal failure (GIF) score, in critically ill patients with severe acute pancreatitis in the Center for Critical Care Medicine, Bach Mai Hospital.Subjects and methods: An observational study was conducted on 96 patients with acute pancreatitis at the Center for Critical Care Medicine, Bach Mai Hospital. The GIF score was assessed daily for the first three days. Monitored outcomes included 28-day mortality and ICU length of stay. Logistic regression was used to evaluate mortality prognosis, and Cox regression was used to assess ICU recovery time, after adjusting for baseline factors such as age and the Marshall score.Results: The study included 96 patients (81.3% male, mean age 46.1 ± 11.8), predominantly with severe acute pancreatitis (87.5%). The 28-day mortality rate was 7.3%, and the mean ICU length of stay was 13.5 ± 10.3 days. The results showed that the mean 3-day GIF score was a statistically significant predictor of recovery time in the ICU (HR = 0.49; 95% CI: 0.36-0.66; p < 0.001). Regarding mortality prognosis, the mean 3-day GIF score was associated with mortality in the univariate analysis (OR = 4.62, p = 0.041) and demonstrated acceptable discriminatory ability (AUC = 0.735, p = 0.039). However, in the multivariable model adjusted for the Marshall score and age, the GIF score was no longer an independent predictor of mortality (p = 0.143).Conclusion: The mean 3-day GIF score is a statistically significant predictor of recovery time for patients with acute pancreatitis in the ICU. However, the prognostic role of the GIF score for the mortality outcome is limited, possibly due to being masked by the condition of systemic multi-organ failure.
Keywords: Acute pancreatitis, gastrointestinal failure, GIF score, prognosis, mortality, ICU.